The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2021
DOI: 10.3389/fped.2021.662165
|View full text |Cite
|
Sign up to set email alerts
|

Association Between the COVID-19 Pandemic and Infant Neurodevelopment: A Comparison Before and During COVID-19

Abstract: Aim: To investigate the association between the experience of the coronavirus disease 2019 (COVID-19) pandemic and neurodevelopment of 6-month-old and 1-year-old children and explore the differences in the association by birth order.Methods: This comparison study was embedded in the Born in Guangzhou Cohort Study in China. The exposed group included 546 6-month-old and 285 1-year-old children who attended neurodevelopment assessments between March 1 and May 15, 2020, and the non-exposed group included 3,009 6-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
63
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(67 citation statements)
references
References 47 publications
3
63
0
1
Order By: Relevance
“…Over the past 20 months, that environment has been fundamentally altered for many children. While the short and long-term neurodevelopmental impacts of the COVID-19 pandemic are not yet well understood in infants and young children (49), emerging reports are suggestive of reduced motor and communication skills (38). Results from this study add to this literature and are in agreement with these past studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Over the past 20 months, that environment has been fundamentally altered for many children. While the short and long-term neurodevelopmental impacts of the COVID-19 pandemic are not yet well understood in infants and young children (49), emerging reports are suggestive of reduced motor and communication skills (38). Results from this study add to this literature and are in agreement with these past studies.…”
Section: Discussionmentioning
confidence: 99%
“…However, emerging results are disturbing. For example, findings from a prenatal cohort in New York City recruiting during the earliest stages of the pandemic reveal reduced motor and cognitive development in infants at 6-months of age (37), and children 6 and 12-months of age born during the pandemic in Guangzhou, China, similarly show reduced communication skills compared to historical references (38).…”
Section: Introductionmentioning
confidence: 99%
“…Early signals of adverse neurodevelopmental outcomes at 3-6 months, 1 year, and 1.5 years in infants and children exposed to SARS-CoV-2 in utero, and/or born during the COVID-19 pandemic are emerging [37][38][39][40][41]. A longitudinal cohort study of 57 infants with prenatal exposure to SARS-CoV-2 in China identified deficits in the social-emotional domain of neurodevelopmental testing at 3 months of age [40].…”
Section: Early Evidence Of Adverse Neurodevelopmental Outcomes In Chi...mentioning
confidence: 99%
“…115 Other preliminary studies have assessed different time periods following delivery, such as 3, 6, and 12 months, and also suggested that SARS-CoV-2 infection during pregnancy can have detrimental impacts on the brain development of the fetus. [116][117][118] Emerging data suggests the Delta variant of SARS-CoV-2 is increasingly associated with severe illness in young children. 119 A large multicenter investigation indicated that COVID-19 was associated with widespread, temporary brain impairment in children and adolescents hospitalized with the virus.…”
Section: Neonatal Infant and Child Outcomes Following Sars-cov-2 Infe...mentioning
confidence: 99%